Anxiety and Body Image in Tattooed and Nontattooed Military Prisoners - Habeger, Terry L. (1972)
Tattooing has evolved into something less than an art, particularity in western cultures, and has lost its original dignity and original significance as well (Abramson,1931). As a result, there has been a great deal of conjecture concerning the psychodynaraics of tattooing (Edgerton & Dingman,1963; Hamburger,1966; Hamburger & Lacovara,1963). The present study was an attempt to investigate the psychodynamics of tattooing through the use of one measure of anxiety and two measures of body image with tattooed and nontattooed individuals. The techniques employed were the Secord (1953) Homonym Word Association Test, the Secord-Jourard (1953) Body Cathexis Scale, and the Taylor (1953) Manifest Anxiety Scale